Effects of Dietary Inclusion of Clostridium autoethanogenum Protein on the Growth Performance and Liver Health of Largemouth Bass (Micropterus salmoides) - Lu, Qisheng; Xi, Longwei; Liu, Yulong; Gong, Yulong; Su, Jingzhi; Han, Dong; Yang, Yunxia; Jin, Junyan; Liu, Haokun; Zhu, Xiaoming; Xie, Shouqi (Frontiers in Marine Science, 2021)
Clostridium autoethanogenum protein (CAP) is a novel protein source for aqua-feeds. The present study aimed to investigate the effects of dietary CAP on growth performance, immunity, and liver health status of juvenile largemouth bass (Micropterus salmoides). Four isonitrogenous and isolipid experimental diets were formulated to replace 0% (D1, control), 25% (D2), 50% (D3), and 75% (D4) of fish meal by CAP. Fish (15.05 ± 0.08 g) were randomly fed one of four experimental diets for 8 weeks. The results showed that weight gain (WG), specific growth rate (SGR), feeding rate (FR), viscerosomatic index (VSI), and hepatosomatic index (HSI) of the D4 group were significantly lower than D1, D2, and D3 groups (P < 0.05). With the increase of substitution level, the total antioxidant capacity (T-AOC) of liver tissue was significantly decreased, while the plasma alkaline phosphatase (AKP) activity was significantly increased (P < 0.05). Plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were significantly higher in D3 and D4 groups than in D1 and D2 groups (P < 0.05). Replacing 50 or 75% fish meal by CAP significantly induced the transcription level of apoptosis-promoting genes (bcl-2-associated death protein [bad] and bcl-2-assoxicated × protein; bag [bax]), anti-apoptosis-related genes (tumor protein 53 [p53] and b-cell lymphoma-2 [bcl-2]), and the apoptotic Caenorhabditis elegans (C. elegans) death gene-3 like caspases (cysteine-aspartic proteases-3 [caspase-3], cysteine-aspartic proteases-8 [caspase-8], cysteine-aspartic proteases-9 [caspase-9], and cysteine-aspartic proteases-10 [caspase-10]) in liver, while suppressed the gene expression of the inflammatory factors [interleukin-1β (il-1β), interleukin-8 (il-8), and tumor necrosis factor, tnf ] in head kidney. At the same time, dietary inclusion of CAP elevated the protein expression of bcl-2, autophagy microtubule-associated protein light chain 3A/B (LC3A/B-I), and LC3A/B-II by inhibiting the phosphorylation of the mammalian target of rapamycin (mTOR; P < 0.05). Moreover, the apoptosis rate of the D3 and D4 groups was significantly increased (P < 0.05). Taken together, these results indicated that the optimal level of CAP-replacing fish meal should be <50% that has no negative effect on the growth performance and liver health of juvenile largemouth bass. In addition, excessive CAP inclusion may damage liver health by activating autophagy and apoptosis signaling pathways.